2009
DOI: 10.5551/jat.e615
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variations of Gastrointestinal Mucosal Damage Detected with Transnasal Endoscopy in Apparently Healthy Subjects Treated with Low-Dose Aspirin (ASA) for a Short Period

Abstract: Aim:In this study, transnasal endoscopy was used to observe the time-course changes of gastrointestinal mucosa with low-dose aspirin (ASA), and the preventive effect of rebamipide was compared with placebo. Methods: Twenty healthy H.pylori-negative subjects were divided between those receiving 100 mg aspirin with placebo, and those receiving 100 mg aspirin 300 mg rebamipide for 7 days daily. Transnasal endoscopy was performed at 0, 2, 6 and 24 hrs on the first day, and then on the third and seventh days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…It is described in the Japanese guidelines for the diagnosis and treatment of gastric ulcer that cessation of NSAIDs is effective for NSAIDsinduced gastrointestinal injury (32); however, to our knowledge, no research has investigated whether L-ASA-induced gastroduodenal mucosal injury would improve with the short cessation of L-ASA, although it is reported that L-ASA induced gastroduodenal mucosal damage for a short period in healthy volunteers (33). In this study, the cessation of L-ASA for seven days was significantly associated with the lower prevalence of L-ASA-induced gastroduodenal ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…It is described in the Japanese guidelines for the diagnosis and treatment of gastric ulcer that cessation of NSAIDs is effective for NSAIDsinduced gastrointestinal injury (32); however, to our knowledge, no research has investigated whether L-ASA-induced gastroduodenal mucosal injury would improve with the short cessation of L-ASA, although it is reported that L-ASA induced gastroduodenal mucosal damage for a short period in healthy volunteers (33). In this study, the cessation of L-ASA for seven days was significantly associated with the lower prevalence of L-ASA-induced gastroduodenal ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…94 Indeed, reversible injury of the upper gastric tract is quite common in Japanese patients treated with low-dose (100 mg/day) aspirin. 95 A prospective registry of Japanese patients taking daily aspirin 96 demonstrated that 6.5% of gastroduodenal ulcers and 29.2% of gastro-enteric erosions, respectively, were detected in 1,454 stable outpatients receiving aspirin for cardioprotective purposes. 97 Proton-pump inhibitors (PPI) are effective in prevention of aspirin-induced gastroduodenal injury, 98 but regular use of PPI is recommended only for high-risk patients.…”
Section: Thrombin Receptor Antagonists and Anticoagulantsmentioning
confidence: 99%
“…Third is the short duration of antiplatelet drug administration. Although Kawai et al [34] reported that peak LDA-induced gastric injury was at 1-3 days later and gastric damage improved gradually in spite of continuous LDA dosage, about 50 and 40% of patients receiving essentially LDA for long periods had esophageal and gastric mucosal injury in study 1. Therefore, we think that further study using many patients is better to clarify whether antiplatelet drug is real risk factor of esophageal injury development or not in both patents infected with H. pylori infection and without, for longer duration in near feature.…”
Section: Discussionmentioning
confidence: 97%